United Kingdom : projected level of demand ,supply,and imports of agricultural products ,1970,1975,and 1980 - University of Oxford Institute for Research in Agricultural Economics; Economic Research Service, U.S. Department of Agriculture (Oxford : University of Oxford Institute for Research in Agricultural Economics, 1969)
The report describes the findings of research on prospective development of the supply and demand for major agricultural products in the United Kingdom
obn 24/01/2019
Loans
Keywords: Farm produce -- Great Britain; Agricultural estimating and reporting -- Great Britain; Agricultural estimating and reporting